Developing training modules for farmer organizations to enhance the local economy - Suhartono Winoto; Asti Amelia Novita; M. R. Khairul Muluk; Oscar Radyan Danar (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
The availability of fertilizer is also a problem experienced by several regions in Indonesia, such as Mrayan Village and Baosan Lor Village, Ponorogo. This availability results in less than optimal quality and quantity of existing harvests. Several stakeholders directed the Association of Farmer Groups (Gapoktan) to optimize existing harvests. This research examines collaboration between relevant stakeholders such as the Department of Agriculture, the Department of Tourism, Perhutani, Extension, and LMDH in overcoming existing problems. One of the efforts is processing household organic waste into eco enzymes or alternative fertilizers that can be used when fertilizer availability is limited. This management requires stakeholders to guide and direct Gapoktan and Gapoktan Perempuan in managing waste and converting it into alternative fertilizers. Based on the program already running, creating a training module that the community can use to continue managing organic waste is necessary. The research was conducted using soft system methodology with the results of a farmer organization governance model through community empowerment. The results show stakeholders' role in providing guidance and direction to farmers through counseling by separating organic and inorganic waste and then processing it into eco enzymes that can be used as alternative fertilizer. Through this research, it is hoped that waste can be processed into alternative fertilizer, but its management requires extension workers and local community leaders. AbstrakKetersediaan pupuk turut menjadi problematika yang dialami oleh beberapa daerah di Indonesia, seperti Desa Mrayan dan Desa Baosan Lor, Ponorogo. Ketersediaan ini menyebabkan kurang optimalnya hasil kualitas dan kuantitas hasil panen yang ada. Menyikapi hal tersebut, beberapa stakeholders mengarahkan Gabungan Kelompok Tani (Gapoktan) untuk mengoptimalkan hasil panen yang ada. Penelitian ini mengkaji kerjasama antara stakeholders terkait seperti Dinas Pertanian, Dinas Pariwisata, Perhutani, Penyuluh hingga LMDH dalam mengatasi problematika yang ada, salah satu upaya yang dilakukan ialah pengolahan sampah organik rumah tangga menjadi eco enzym atau pupuk alternatif yang dapat digunakan dikala ketersediaan pupuk sedang terbatas. Pengelolaan ini membutuhkan peran dari stakeholders untuk membimbing dan mengarahkan Gapoktan dan Gapoktan Wanita dalam mengelola sampah menjadi pupuk alternatif. Adapun berdasarkan program yang telah berjalan, perlu dibuat suatu modul pelatihan yang dapat digunakan masyarakat untuk melanjutkan pengelolaan sampak organik. Penelitian yang dilakukan menggunakan metode soft system methodology dengan hasil berupa model tata kelola organisasi petani melalui pemberdayaan masyarakat. Hasil yang didapat, adanya peran dari stakeholders dalam memberikan bimbingan dan arahan kepada para petani melalui penyuluhan dengan memisahkan sampah organik dan anorganik untuk kemudian diolah menjadi eco enzym yang dapat dimanfaatkan sebagai pupuk alternatif. Melalui penelitian ini, diharapkan sampah dapat diolah menjadi pupuk alternatif, namun dalam pengelolaannya dibutuhkan adanya peran dari penyuluh dan tokoh masyarakat setempat.Kata Kunci: modul pengembangan masyarakat; model tata kelola; stakeholders